Transmission Performance Analysis of Fiber Optical Parametric Amplifiers for WDM System. (30th March 2009) - Jiang, Xiaohong; Jiang, Chun
Abstract : A numerical analysis is presented on the long-haul wavelength-division multiplexing (WDM) transmission system employing fiber-optic parametric amplifier (FOPA) cascades based on one-pump FOPA model with Raman Effect taken into account. The end-to-end equalization scheme is applied to optimize the system features in terms of proper output powers and signal-to-noise ratios (SNRs) in all the channels. The numerical results show that—through adjusting the fiber spans along with the number of FOPAs as well as the channel powers at the terminals in a prescribed way—the transmission distance and system performance can be optimized. By comparing the results generated by different lengths of fiber span, we come to the optimal span length to achieve the best transmission performance. Furthermore, we make a comparison among the long-haul WDM transmission systems employing different inline amplifiers, namely, FOPA, erbium-doped fiber amplifier (EDFA), and Fiber Raman Amplifier (FRA). FOPA demonstrates its advantage over the other two in terms of system features.